Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.31219/osf.io/txe89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stroke rehabilitation use and caregiver psychosocial health profiles in Singapore: A latent profile transition analysis

Abstract: Objectives: To identify and describe the transition of latent profiles characterized by caregiver psychosocial health characteristics over a 12-month period, to determine if stroke rehabilitation use at 12-month post-stroke differed by profile transition patterns, and to investigate if the identified profiles at 3-month post-stroke influence the explanation of stroke rehabilitation use at 12-month post-stroke by stroke rehabilitation use at 3-month post-stroke, with covariates.Design: Latent profile transition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…18,19 Recent research found that Singapore caregivers of stroke survivors who were distressed at hospital discharge had a 24% likelihood of remaining distressed 12 months after discharge. 20,21 The proposed national study should include a time dimension, and ask if caregiver well-being fluctuates similarly when the care recipient suffers from other chronic conditions or disabilities, and if this trend persists over a longer time horizon.…”
Section: Make Evidence-based Policymentioning
confidence: 99%
“…18,19 Recent research found that Singapore caregivers of stroke survivors who were distressed at hospital discharge had a 24% likelihood of remaining distressed 12 months after discharge. 20,21 The proposed national study should include a time dimension, and ask if caregiver well-being fluctuates similarly when the care recipient suffers from other chronic conditions or disabilities, and if this trend persists over a longer time horizon.…”
Section: Make Evidence-based Policymentioning
confidence: 99%
“…Globally, stroke is the second leading cause of death [1] and poses a serious burden to the caregivers and society [2,3]. Ischemic stroke accounts for more than 70% of strokes [4].…”
Section: Introductionmentioning
confidence: 99%